2019
DOI: 10.4314/ovj.v9i3.12
|View full text |Cite
|
Sign up to set email alerts
|

<i>Salmonella enterica</i> and <i>Theileria</i> co-infection in dromedary camels (<i>Camelus dromedarius</i>) in UAE

Abstract: Background: Despite a steady increase in camel husbandry worldwide, pathology of camel diseases is still relatively under-investigated. Clinical hematuria is generally indicative of either acute or chronic urogenital inflammations, traumatic calculous injuries, cancers, corrosive poisonings. Infectious agents are not typically implicated in urinary tract infection of camels. Aim: This study aims to explore possible causes in camels clinically suffered from acute febrile disease with severe hematuria. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In TSI all isolates appear alkaline/ acid, black respectively with gas formation, yellow color resulting from fermentation glucose, black color result as formation of H2S from iron of media and gas formation come from sucrose fermentation (Abdelwahab et al, 2019) (Lamas et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In TSI all isolates appear alkaline/ acid, black respectively with gas formation, yellow color resulting from fermentation glucose, black color result as formation of H2S from iron of media and gas formation come from sucrose fermentation (Abdelwahab et al, 2019) (Lamas et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Sequence analysis confirmed 100% identity to T. annulata isolates from cattle [ 11 ]. Abdelwahab and colleagues [ 14 ] reported coinfection of salmonellosis and theileriosis in camels in UAE that clinically suffered from acute febrile disease with severe hematuria.…”
Section: Discussionmentioning
confidence: 99%
“…in camels [ 11 , 12 , 13 ]. Incidence of clinical theileriosis in dromedary camels have been reported in the United Arab Emirates [ 14 ]. T. annulata antigen was detected in Hyalomma dromedarii ticks in the Eastern region of Abu Dhabi [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…As in this study, salmonellosis in dromedaries is generally asymptomatic, although clinical Salmonella infections have been reported with symptoms that included epiphora, anorexia, muscle twitching and lateral recumbency (Nour‐Mohammadzadeh et al., 2010). In addition, controlling Salmonella infections in camels should be taken into account, as it has been shown that Salmonella could be the cause of co‐infections such as clostridia or theileriosis diseases (Abdelwahab et al., 2019). Regarding Salmonella serovars isolated, ser.…”
Section: Discussionmentioning
confidence: 99%